Parenetična retorika v govorih In Matthaeum Janeza Krizostoma - Bogataj, Jan Dominik (Primerjalna književnost, 2019)
The article examines the relation between classical pagan and Christian rhetoric in the late antiquity through the case study of literary genres of moral exhortation in the homilies of John Chrysostom (347-407). First, it discusses the elements of diatribe, lalia and protrepticus as rhetorical forms of parenetical and counselling (psyhogogical) character which were partly already known the traditional classical Greek rhetoric and partly developed by the circles of late antique Hellenistic philosophers and theoreticians of rhetoric and style. The second aim of the article is to show in what measure these genres are present in the Chrysostome's elocutio in the homilies In Matthaeum (Hom. 1, 7, 23). By doing this, the author presents some new insights on the influence of pagan rhetoric on the Golden Mouth which uses some the pagan literary forms to shape his moral exhortation, but he does this in a genuine style.
Keywords: ekshortacija; Ioannes Chrysostomus; klasična retorika; krščansko govorništvo; pridige; retorične oblike; zgodnjekrščanska književnost